Structural And Semantic Analyses Of Shortened Slang Words. - Bunyodbek Sotvoldiyev (International Journal of Advanced Science and Technology, 2020)
This article deals with the problem of the structural and semantic analyses of shortened slang words. It is obvious that shortening has a great role in a new word-building process in English lexicology. Ergo, the number of investigations devoted to the slang or shortened words in the realm of the English linguistics has increased dramatically for a couple of decades. Although much attention has been given to this sphere, the number of scientific researches relevant to the very structural and semantic analyses of the shortened words in slang lacks.